Halogen-free flame-retardant resin composition and wiring material using same

A balanced resin composition using ethylene vinyl acetate, acidic polyolefin polymer, metal hydrate, and additives achieves both excellent flame retardancy and mechanical strength in wiring materials, addressing molding challenges.

JP7623184B2Active Publication Date: 2025-01-28FURUKAWA ELECTRIC CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2021055915
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-03-29
Publication Date
2025-01-28
Estimated Expiration
2041-03-29

AI Technical Summary

Technical Problem

Non-halogen-based flame-retardant resin compositions face challenges in achieving a balance between excellent flame retardancy and mechanical characteristics, leading to high viscosity and difficulty in molding, which affects the production of wiring materials.

Method used

A resin composition combining ethylene vinyl acetate copolymer, acidic polyolefin polymer, metal hydrate, clay minerals, and 4th grade ammonium salt, with specific ratios to enhance melt flow rate and balance flame retardancy and mechanical properties.

Benefits of technology

The composition allows for smooth molding without excessive load, producing wiring materials with high flame retardancy and mechanical strength, suitable for coating layers in conductors and optical cables.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007623184000003
    Figure 0007623184000003
  • Figure 0007623184000004
    Figure 0007623184000004
  • Figure 0007623184000001
    Figure 0007623184000001
Patent Text Reader

Abstract

To provide a non-halogen-based flame-retardant resin composition which enables molding of a molded body excellent in flame retardancy and mechanical characteristics, and a wiring material having a coating layer formed from the composition.SOLUTION: There are provided a non-halogen-based flame-retardant resin composition which contains, with respect to 100 pts.mass of a base resin containing 60-100 mass% of an ethylene vinyl acetate copolymer having an MFR of 2-15 g / 10 min, 20 mass% or less of an acid-modified polyolefin polymer and 20 mass% or less of an α-olefin polymer, 100-250 pts.mass of a metal hydrate, and 2-30 pts.mass of the total amount of a clay mineral and a quaternary ammonium salt, and has an MFR of 0.3 g / 10 min or more; and a wiring material having a coating layer formed from the composition on an outer peripheral surface of a conductor.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a halogen-free flame-retardant resin composition and a wiring material using the same. [Background technology]

[0002] Wiring materials (insulated wires or cables, (electrical) cords, optical fiber cords, optical cables, etc.) are used to transport power and transmit information. In particular, optical fiber transmission is the mainstream for transmitting information due to its large transmission capacity and low transmission loss. Among optical fibers, multi-core optical fiber cables (also called optical cables) containing many optical fiber cores or optical fiber ribbon cores are used for large-capacity transmission over long distances. For example, data centers that centrally manage information are built and operated in various locations, and the amount of information handled there is enormous, so multi-core optical cables are used for transmitting information between data centers. Similarly, optical cables are also used for transmitting information between data servers within a data center. These wiring materials are usually provided with a coating layer formed of various resin compositions on the outer peripheral surface of the conductor or fiber core, etc., to protect the conductor or fiber core and ensure electrical insulation. In addition, wiring materials arranged in houses such as data centers, particularly optical cables, require flame-retardant wiring materials having a coating layer formed of a flame-retardant resin composition in order to prevent the spread of fire in the event of a fire. Furthermore, the use of non-halogen flame retardant materials that do not contain halogen-containing flame retardants, which are said to generate less smoke and less toxic gases, is recommended not only to prevent the spread of fire in the event of a fire but also to prevent human damage. For such a coating layer, a resin composition containing a non-halogen flame retardant, a metal hydrate, and various additives as a flame retardant has been studied. For example, Patent Document 1 describes a non-halogen flame retardant resin composition obtained by adding a metal hydroxide surface-treated with a specific amount of a fatty acid-based treatment agent and a silane coupling agent to a polyolefin resin, the non-halogen flame retardant resin composition being formed by adding 150 to 300 parts by mass of the metal hydroxide, 0.5 to 10 parts by mass of a hindered phenol-based antioxidant, and 0.2 to 5 parts by mass of a sulfur-based antioxidant to 100 parts by mass of the polyolefin resin. Patent Document 2 also describes a resin composition containing a clay mineral and a quaternary ammonium salt in a total amount of 2 to 15 parts by mass to 100 parts by mass of a base resin, the base resin containing 10 to 30% by mass of an acid-modified polyolefin resin and 70 to 90% by mass of a polyolefin resin (X) other than the acid-modified polyolefin resin. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2009-084524 A [Patent Document 2] JP 2020-164695 A Summary of the Invention [Problem to be solved by the invention]

[0004] Although it depends on the type of flame retardant, the mechanism of flame retardancy, etc., halogen-free flame-retardant resin compositions usually contain a large amount of flame retardant to exhibit a desired flame retardancy. Therefore, the melt viscosity of the halogen-free flame-retardant resin composition is high, and it is difficult to manufacture (mold) the wiring material without applying an excessive load (poor moldability), and even if it can be manufactured, it is not possible to realize the desired shape and dimensions. In addition, if a large amount of metal hydroxide is contained as a flame retardant, the mechanical properties, especially the mechanical strength, of the coating layer formed from the halogen-free flame-retardant resin composition are reduced, and the required properties of the wiring material cannot be satisfied. Thus, there is a trade-off between the moldability of the halogen-free flame-retardant resin composition and the flame retardancy and mechanical properties of the molded product, and it is desirable to achieve both. However, Patent Documents 1 and 2 do not consider this point of view.

[0005] The present invention aims to provide a non-halogen flame-retardant resin composition capable of forming a molded article having excellent flame retardancy and mechanical properties. Another object of the present invention is to provide a wiring material having a coating layer having excellent flame retardancy and mechanical properties formed using the non-halogen flame-retardant resin composition. [Means for solving the problem]

[0006] The present inventors have intensively studied non-halogen flame retardant resin compositions and have come to the conclusion that the moldability, flame retardancy, and mechanical properties cannot be balanced by simply setting the type (combination) and content of the non-halogen flame retardant and metal hydrate such as metal hydroxide. Therefore, as a result of further investigation, the inventors have come up with the idea that moldability, flame retardancy, and mechanical properties can be balanced by combining the metal hydrate with a non-halogen flame retardant consisting of a clay mineral and a quaternary ammonium salt and then mixing it with a base resin containing an ethylene-vinyl acetate copolymer exhibiting a specific melt flow rate (MFR). As a result of further investigation based on this idea, the inventors have found that by containing a metal hydrate, the non-halogen flame retardant, and an ethylene-vinyl acetate copolymer as a base resin in a specific ratio, moldability, flame retardancy, and mechanical properties can be balanced, and a wiring material (coating layer) having excellent mechanical properties and flame retardancy can be produced with high productivity (while achieving high moldability). Based on this finding, the present inventors conducted further research and have now completed the present invention.

[0007] That is, the object of the present invention has been achieved by the following means. <1> For 100 parts by mass of a base resin containing 60 to 100% by mass of an ethylene-vinyl acetate copolymer having a melt flow rate (measurement temperature: 190°C, load: 2.16 kg) of 2 to 15 g / 10 min, 20% by mass or less of an acid-modified polyolefin polymer, and 20% by mass or less of an α-olefin polymer, The composition contains 100 to 250 parts by mass of a metal hydrate, and 2 to 30 parts by mass of a clay mineral and a quaternary ammonium salt in total, A halogen-free, flame-retardant resin composition having a melt flow rate (measurement temperature: 190°C, load: 10 kg) of 0.3 g / 10 min or more. <2> The α-polyolefin polymer comprises at least one of polyethylene and polypropylene; <1> 2. The halogen-free flame-retardant resin composition according to claim 1 . <3> The acid-modified polyolefin polymer contains at least one of maleic anhydride-modified polyethylene, acrylic acid-modified polyethylene, maleic anhydride-modified polypropylene, and acrylic acid-modified polypropylene. <1> or <2> 2. The halogen-free flame-retardant resin composition according to claim 1 . <4> A wiring material having a coating layer on an outer peripheral surface of a conductor, The coating layer is <1> ~ <3> 2. A wiring material formed from the halogen-free flame-retardant resin composition according to claim 1. <5> The wiring material is an insulated wire or a power cable. <4> The wiring material according to claim 1. <6> The wiring material is an optical cable. <4> or <5> The wiring material according to claim 1.

[0008] In this specification, a numerical range expressed using "to" means a range that includes the numerical values ​​before and after "to" as the lower and upper limits. Effect of the Invention

[0009] The non-halogenous flame-retardant resin composition of the present invention can form a coating layer (molded product) having excellent flame retardancy and mechanical properties while realizing high moldability that enables smooth molding without applying excessive load. Also, the wiring material of the present invention has a coating layer having excellent flame retardancy and mechanical properties formed using the non-halogenous flame-retardant resin composition. [Brief description of the drawings]

[0010] [Figure 1] FIG. 1 is a cross-sectional view showing the structure of one embodiment of the optical cable of the present invention. [Diagram 2] FIG. 2 is a cross-sectional view showing the structure of another embodiment of the optical cable of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] [Halogen-free flame-retardant resin composition] The non-halogen-based flame-retardant resin composition of the present invention is a resin composition containing 100 parts by mass of a base resin containing 60 to 100 parts by mass of an ethylene-vinyl acetate copolymer having an MFR (measurement temperature 190°C, load 2.16 kg) of 2 to 15 g / 10 min, 20 parts by mass or less of an acid-modified polyolefin polymer, and 20 parts by mass or less of an α-olefin polymer, 100 to 250 parts by mass of a metal hydrate, and 2 to 30 parts by mass of a clay mineral and a quaternary ammonium salt (total amount), and shows an MFR of 0.3 g / 10 min or more (measurement temperature 190°C, load 10 kg). As a result, the above-mentioned components contained in a specific ratio (content) synergistically perform each function to express the above-mentioned MFR, and as a result, the non-halogen-based flame-retardant resin composition can express excellent moldability, high flame retardancy, and excellent mechanical properties (especially high mechanical strength) in a well-balanced manner. Since the halogen-free flame-retardant resin composition of the present invention does not contain any halogen-based flame retardant or flame retardant assistant, it is possible to suppress the generation of smoke and toxic gases resulting from these. Therefore, by using the halogen-free flame-retardant resin composition of the present invention, a coating layer exhibiting high flame retardancy and excellent mechanical properties (particularly high mechanical strength), and further a wiring material having this coating layer, can be produced with high productivity (while realizing high moldability that enables smooth molding without applying excessive load). Thus, the halogen-free flame-retardant resin composition of the present invention is suitable as a composition for (extrusion) molding, and further suitable as a material for forming a coating layer for wiring materials (material for forming an extrusion coating layer).

[0012] The halogen-free resin composition of the present invention exhibits an MFR (measurement temperature 190°C, load 10 kg) of 0.3 g / 10 min or more, and exhibits excellent moldability. The MFR (measurement temperature 190°C, load 10 kg) of the halogen-free resin composition of the present invention is preferably 0.5 g / 10 min or more, more preferably 0.75 g / 10 min or more, from the viewpoint of further improving moldability. On the other hand, the upper limit of the MFR is practically 2.5 g / 10 min or less, from the viewpoint of suppressing a decrease in flame retardancy (particularly by preventing sagging in a flame retardancy test), preferably 1.5 g / 10 min or less, and more preferably 1.0 g / 10 min or less, from the viewpoint of maintaining excellent flame retardancy. The MFR of the halogen-free resin composition can be appropriately adjusted depending on the components contained in the halogen-free resin composition, particularly the base resin, the type and content of the metal hydrate, and further the type and content of the lubricant component, the clay mineral, and the quaternary ammonium salt, etc. For example, the MFR of the halogen-free resin composition can be increased by increasing the content of the ethylene-vinyl acetate copolymer in the base resin, increasing the MFR of the ethylene-vinyl acetate copolymer, or further increasing the content of a copolymer exhibiting a high MFR. In the present invention, the MFR of the copolymer or resin composition is a value measured based on the method specified in Japanese Industrial Standards (JIS) K 7210-1 under conditions of a measurement temperature of 190° C. and a load of 10 kg or 2.16 kg.

[0013] Each component used in the present invention and its content will be described below. <Base resin> The base resin that serves as the base for the halogen-free flame-retardant resin composition of the present invention or its molded article contains 60 to 100 parts by mass of an ethylene-vinyl acetate copolymer having an MFR (measurement temperature: 190°C, load: 2.16 kg) of 2 to 15 g / 10 min, 20 parts by mass or less of an acid-modified polyolefin polymer, and 20 parts by mass or less of an α-olefin polymer.

[0014] (Ethylene vinyl acetate copolymer) The ethylene-vinyl acetate copolymer may be any copolymer (usually a resin) of ethylene and vinyl acetate, and may be an alternating copolymer in which an ethylene component and a vinyl acetate component are polymerized alternately, a block copolymer in which a polymerized block of an ethylene component and a polymerized block of a vinyl acetate component are bonded, or a random copolymer in which an ethylene component and a vinyl acetate component are polymerized randomly.

[0015] The ethylene-vinyl acetate copolymer used has an MFR of 2 g / 10 min or more (measurement temperature 190° C., load 2.16 kg) measured by the above method. This allows the MFR of the halogen-free flame-retardant resin composition to be adjusted to the above range, contributing to the realization of excellent moldability. The MFR of the ethylene-vinyl acetate copolymer is 2 to 15 g / 10 min in order to achieve a good balance between moldability, flame retardancy, and mechanical properties, and is preferably 3 to 10 g / 10 min, more preferably 4 to 10 g / 10 min in order to achieve a good balance between the above properties at a high level. By incorporating an ethylene-vinyl acetate copolymer as a base resin in a specific content described below into the halogen-free flame-retardant resin composition having the above composition and MFR, the MFR of the composition can be increased even if it contains a metal hydrate, thereby improving moldability, and also improving flame retardancy and mechanical properties.

[0016] The vinyl acetate content (also referred to as VA content) of the ethylene-vinyl acetate copolymer is not particularly limited and is appropriately determined in consideration of the MFR of the copolymer, as well as moldability, flame retardancy, and mechanical properties. For example, in the present invention, the VA content is preferably 20 to 35 mass% in the ethylene-vinyl acetate copolymer, and more preferably 25 to 30 mass%. The vinyl acetate content in the ethylene-vinyl acetate copolymer can be determined in accordance with JIS K 7192.

[0017] The ethylene-vinyl acetate copolymer contained as the base resin may be one type or two or more types. When the halogen-free flame-retardant resin composition (base resin) of the present invention contains two or more kinds of ethylene-vinyl acetate copolymers, it is preferable that all of the ethylene-vinyl acetate copolymers satisfy the above-mentioned range of vinyl acetate content and further the above-mentioned range of VA amount, but it is also possible to contain an ethylene-vinyl acetate copolymer that does not satisfy the vinyl acetate content or VA amount. In this case, it is preferable that the ethylene-vinyl acetate copolymer as a whole satisfies the above-mentioned range of vinyl acetate content and further the above-mentioned range of VA amount.

[0018] The content of the ethylene-vinyl acetate copolymer is 60 to 100 mass% in 100 mass% of the base resin, and from the viewpoint of achieving high levels of flame retardancy and mechanical properties while maintaining moldability, it is preferably 65 to 90 mass%, and more preferably 75 to 85 mass%.

[0019] (Acid-modified polyolefin polymer) As the acid-modified polyolefin polymer, a polymer (usually a resin) obtained by modifying a polyolefin polymer described below with an unsaturated carboxylic acid compound (also simply called unsaturated carboxylic acid) or an anhydride thereof can be suitably used. By incorporating an acid-modified polyolefin polymer as a base resin in a specific content described below in the halogen-free flame-retardant resin composition having the above-mentioned composition and MFR, it is possible to improve mechanical properties, particularly mechanical strength, while maintaining excellent moldability and flame retardancy.

[0020] The polyolefin polymer to be modified with an acid is not particularly limited as long as it is an α-olefin polymer, and examples thereof include the α-olefin polymers described below. From the viewpoint of enhancing mechanical properties, polyethylene or polypropylene is preferred. The polyolefin polymer forming the acid-modified polyolefin resin may be one type or two or more types. The unsaturated carboxylic acid (including anhydride) forming the acid-modified polyolefin resin is not particularly limited, and a suitable example is a carboxylic acid having an unsaturated bond capable of reacting (for example, radical addition reaction) with the polyolefin polymer. The unsaturated carboxylic acid may have one or more carboxy groups. Specific examples of preferred unsaturated carboxylic acids include acrylic acid, methacrylic acid, maleic acid, itaconic acid, and fumaric acid, as well as metal salts or organic salts thereof, and unsaturated carboxylic acid anhydrides such as maleic anhydride, itaconic anhydride, and fumaric anhydride. These unsaturated carboxylic acids may be used alone or in combination of two or more. The acid-modified polyolefin polymer has a group derived from the unsaturated carboxylic acid, usually as a side chain (pendant chain, graft chain, etc.), as a result of reaction of the unsaturated group of the unsaturated carboxylic acid with the above-mentioned polyolefin polymer.

[0021] From the viewpoint of affinity with clay minerals, the acid-modified polyolefin polymer is preferably at least one of polyethylene or polypropylene modified with maleic anhydride or acrylic acid. That is, in the halogen-free flame-retardant resin composition of the present invention, the acid-modified polyolefin polymer preferably contains at least one of maleic anhydride-modified polyethylene, acrylic acid-modified polyethylene, maleic anhydride-modified polypropylene, and acrylic acid-modified polypropylene. Among them, maleic anhydride-modified polyethylene is preferred because of its high effect of improving mechanical properties (mechanical strength). The amount of modification with the unsaturated carboxylic acid in the acid-modified polyolefin polymer is not particularly limited, but is preferably 0.1 to 2.0 mass %, more preferably 0.2 to 1.0 mass %, based on the polyolefin polymer (before modification).

[0022] The acid-modified polyolefin polymer may be appropriately synthesized or a commercially available product may be used. When synthesizing the acid-modified polyolefin polymer, the polyolefin polymer and the unsaturated carboxylic acid are usually heated and mixed in the presence of an organic peroxide at a temperature equal to or higher than the decomposition temperature of the organic peroxide to modify the polyolefin polymer (react with the unsaturated carboxylic acid) to obtain the acid-modified polyolefin polymer.

[0023] The acid-modified polyolefin polymer contained as the base resin may be one type or two or more types. The content of the acid-modified polyolefin polymer is 20% by mass or less in 100% by mass of the base resin, and is preferably 5 to 20% by mass, more preferably 5 to 15% by mass, and even more preferably 8 to 12% by mass, in order to maintain moldability and flame retardancy while improving mechanical properties, particularly mechanical strength.

[0024] (α-olefin polymer) The α-olefin polymer is a polymer (usually a resin) obtained by homopolymerizing or copolymerizing an α-olefin compound having an ethylenically unsaturated bond at its terminal (usually an alkene having an ethylenically unsaturated bond at its terminal), and is not particularly limited as long as it is not acid-modified, and conventionally known polymers can be used. In the present invention, "not acid-modified" includes not only an embodiment in which the modification amount of the α-olefin polymer is 0% by mass, but also an embodiment in which the α-olefin polymer is acid-modified to an extent that can be distinguished from the above-mentioned acid-modified polyolefin polymer (for example, the modification amount is less than 0.1% by mass). Examples of the α-olefin polymer preferably used in the present invention include various resins such as polyethylene, polypropylene, and copolymers having an acid copolymer component (including an acid ester copolymer component).

[0025] The α-olefin polymer contained as the base resin may be one type or two or more types. In the present invention, it is preferable to use polyethylene and polypropylene in combination as the α-olefin polymer. The total content of the α-olefin polymers is 20% by mass or less in 100% by mass of the base resin, and is preferably 5 to 20% by mass in order to broaden the temperature range in which good molded body surface properties can be obtained, and more preferably 5 to 15% by mass in consideration of the effect on combustion properties.

[0026] - Polyethylene - The polyethylene may be any polymer containing an ethylene component, including a homopolymer of ethylene (homopolyethylene), a copolymer of ethylene and an α-olefin other than ethylene (preferably 5 mol% or less) (ethylene-α-olefin copolymer) (excluding those corresponding to polypropylene described later), and a copolymer of ethylene and a non-olefin having only carbon atoms, oxygen atoms, and hydrogen atoms in the functional group (preferably 1 mol% or less). The above-mentioned α-olefins and non-olefins are not particularly limited to known ones that are conventionally used as copolymerization components of polyethylene. For example, the α-olefin is not particularly limited, but may be an α-olefin having 3 to 12 carbon atoms (specifically, 1-propylene, 1-butene, 1-hexene, 4-methyl-1-pentene, 1-octene, 1-decene, or 1-dodecene). As the ethylene-α-olefin copolymer, a preferred example is a copolymer of ethylene and the above-mentioned α-olefin having 3 to 12 carbon atoms (excluding those corresponding to polypropylene described later).

[0027] As the polyethylene, ethylene homopolymers and ethylene-α-olefin copolymers are preferred, and among them, high density polyethylene (HDPE), low density polyethylene (LDPE), linear low density polyethylene (LLDPE) or very low density polyethylene (VLDPE) are more preferred, and linear low density polyethylene is particularly preferred.

[0028] The polyethylene contained as the base resin may be one type or two or more types. The content of polyethylene is appropriately determined in consideration of the total content of the α-olefin polymers. For example, it is 20% by mass or less in 100% by mass of the base resin, and is preferably 0 to 15% by mass or less, more preferably 5 to 15% by mass, and even more preferably 8 to 10% by mass, in order to broaden the extrusion temperature range within a range that does not adversely affect flammability.

[0029] - Polypropylene - The polypropylene may be any polymer containing a propylene constituent as the main component, and includes a propylene homopolymer (homopolypropylene), an ethylene-propylene random copolymer, an ethylene-propylene block copolymer, and the like. The ethylene-propylene random copolymer refers to one having an ethylene component content of about 1 to 10% by mass, and the ethylene component is randomly incorporated into the propylene chain. Here, the ethylene component content is a value measured in accordance with the method described in ASTM D3900. The ethylene-propylene block copolymer refers to one having an ethylene or ethylene-propylene rubber (EPR) component content of about 5 to 20% by mass, and refers to one having an island-sea structure in which the ethylene or EPR component exists independently within the propylene component.

[0030] As the polypropylene, an ethylene-propylene random copolymer is preferred in terms of extrusion surface properties.

[0031] The polypropylene contained as the base resin may be one type or two or more types. The content of polypropylene is appropriately determined in consideration of the total content of the α-olefin polymers. For example, in 100% by mass of the base resin, it is 15% by mass or less, and from the viewpoint of improving the extrusion surface property without adversely affecting the flammability, it is preferably 0 to 15% by mass or less, more preferably 2 to 12% by mass, and even more preferably 3 to 10% by mass. When the α-olefin polymer contains polyethylene and polypropylene, the ratio of the above polyethylene content to the above polypropylene content [the above polyethylene content / the above polypropylene content] is appropriately determined, but is preferably, for example, 0.5 to 3, and more preferably 0.8 to 1.2.

[0032] - Polyolefin copolymer containing an acid copolymer component - The acid copolymerization component constituting the polyolefin copolymer having an acid copolymerization component is incorporated into the main chain, and in this respect, it is different from the above-mentioned acid-modified polyolefin polymer. The acid copolymerization component is not particularly limited, but includes carboxylic acid compounds such as (meth)acrylic acid, and (meth)acrylic acid alkyl ester compounds. Here, the alkyl group of the (meth)acrylic acid alkyl is preferably one having 1 to 12 carbon atoms. Examples of the polyolefin copolymer having an acid copolymerization component include ethylene-(meth)acrylic acid copolymer, ethylene-(meth)acrylic acid alkyl copolymer, and the like.

[0033] The polyolefin copolymer resin having an acid copolymerization component contained as the base resin may be one type or two or more types. The content of the polyolefin copolymer having an acid copolymerization component is appropriately determined taking into consideration the total content of the α-olefin polymer, for example, 20% by mass or less, preferably 0 to 10% by mass or less, in 100% by mass of the base resin.

[0034] <Metal hydrate> The halogen-free flame-retardant resin composition of the present invention contains a metal hydrate. As the metal hydrate, any metal hydrate that is usually used as a filler in a resin composition can be used without any particular limitation. Examples of such metal hydrates include metal hydrates such as compounds having hydroxyl groups or water of crystallization, such as aluminum hydroxide, magnesium hydroxide, calcium carbonate, magnesium carbonate, calcium silicate, magnesium silicate, hydrated aluminum silicate, hydrated magnesium silicate, and hydrotalcite.

[0035] The metal hydrate may be one that has been surface-treated with a silane coupling agent or the like. Examples include Kisuma 5L and Kisuma 5P (both trade names, magnesium hydroxide, manufactured by Kyowa Chemical Industry Co., Ltd.). The amount of the silane coupling agent used to treat the surface of the metal hydrate is not particularly limited, but is preferably, for example, 3 mass% or less. The metal hydrate is usually contained as a powder or particles. The average particle size in this case is not particularly limited, but is preferably 0.2 to 10 μm. If the average particle size is within the above range, secondary aggregation can be suppressed. The average particle size is determined by dispersing the inorganic filler in alcohol or water and using an optical particle size measuring device such as a laser diffraction / scattering type particle size distribution measuring device.

[0036] Among the above-mentioned metal hydrates, metal hydroxides such as aluminum hydroxide and magnesium hydroxide are preferred, and magnesium hydroxide is preferred because it has a high ability to form a shell when burned and exhibits high flame retardancy. On the other hand, the present invention makes it possible to realize high flame retardancy while maintaining moldability and mechanical properties by using the metal hydrate in combination with a flame retardant auxiliary containing a clay mineral and a quaternary ammonium salt, which will be described later, and a specific base resin. Therefore, even if the metal hydrate contains aluminum hydroxide, which has a shell-forming ability inferior to magnesium hydroxide when burned, the low shell-forming ability can be reinforced to achieve the desired high flame retardancy. That is, according to the present invention, the flame retardancy, which is likely to decrease when aluminum hydroxide, which has a poor shell-forming ability, is used, can be increased, and a high flame retardancy improvement effect can be exhibited. In this respect, in the present invention, aluminum hydroxide, which is inexpensive and highly versatile, can be preferably used as the metal hydrate.

[0037] The halogen-free flame-retardant resin composition of the present invention may contain one or more types of metal hydrates. The content of the metal hydrate in the halogen-free flame-retardant resin composition is 100 to 250 parts by mass relative to 100 parts by mass of the base rubber. Within this range, the deterioration of mechanical properties due to the inclusion of the metal hydrate can be suppressed. The lower limit of the content is preferably 120% by mass or more, more preferably 140% by mass or more, and even more preferably 160% by mass or more, in order to enable high flame retardancy while maintaining mechanical properties and moldability. On the other hand, the upper limit is preferably 220% by mass or less, more preferably 200% by mass or less, and even more preferably 180% by mass or less, in order to suppress the deterioration of moldability due to a decrease in the MFR of the composition.

[0038] <Clay minerals and quaternary ammonium salts> The non-halogen flame-retardant resin composition of the present invention contains a clay mineral and a quaternary ammonium salt. The clay mineral and the quaternary ammonium salt, which coexist with each other, work together with the base resin and the metal hydrate to enhance the flame retardancy of the non-halogen flame-retardant resin composition. In particular, even if the ethylene-vinyl acetate copolymer is used at a high content as the base resin, the reduction in flame retardancy (reduction in shell-forming ability) of the non-halogen flame-retardant resin composition due to the inclusion of this copolymer is reinforced, and excellent flame retardancy (for example, drip prevention action in the flame retardancy test in the examples described later) can be maintained. Furthermore, mechanical properties can also be improved. The form in which the clay mineral and the quaternary ammonium salt are contained or present in the non-halogen flame-retardant resin composition and its molded body (coating layer) is not particularly limited, and examples thereof include a form in which each of them is contained or present alone, a form in which they are contained or present in the form of a mixture or complex, and a form in which these forms coexist. Here, the mixture or complex refers to a clay mineral and a quaternary ammonium salt, and may be formed of a clay mineral and an ion constituting a quaternary ammonium salt. Examples of such a mixture or complex include those obtained by treating a clay mineral with a quaternary ammonium salt under normal conditions, and specifically include BYK-MAX CT 4260 (trade name, manufactured by BYK), RXG7581 (trade name, manufactured by BYK, bentonite treated with dialkyldimethylammonium salt (CAS.61789-80-8)), Kunipia F, Kunipia G, Kunipia G4, Kunipia G10 (all trade names, manufactured by Kunimine Kogyo Co., Ltd.), and the like.

[0039] The clay mineral and the quaternary ammonium salt (mixture or complex, etc.) contained in the halogen-free flame-retardant resin composition of the present invention may be one type or two or more types. The total content of the clay mineral and the quaternary ammonium salt in the non-halogen flame-retardant resin composition is 2 to 30 parts by mass relative to 100 parts by mass of the base rubber. This allows the moldability, flame retardancy, and mechanical properties to be balanced in cooperation with a specific amount of the base resin and metal hydrate. The lower limit of the total content is preferably 8% by mass or more, more preferably 10% by mass or more, and even more preferably 12% by mass or more, in order to enable high flame retardancy while maintaining mechanical properties and moldability. On the other hand, the upper limit is preferably 20% by mass or less, more preferably 18% by mass or less, and even more preferably 15% by mass or less, in order to suppress deterioration of moldability while maintaining excellent flame retardancy and mechanical properties. The ratio of the contents of the clay mineral and the quaternary ammonium salt (clay mineral:quaternary ammonium salt, mass ratio) is not particularly limited, but is preferably, for example, 90:10 to 60:40.

[0040] (Clay Minerals) The clay mineral cooperates with metal hydrates and the like to contribute to improving the flame retardancy of the non-halogen flame-retardant resin composition. The clay mineral can be any clay mineral that is commonly used in resin compositions without any particular restrictions. Clay minerals containing silicate minerals as the main component are preferred, and clay minerals containing silicate minerals having a layered crystal structure are more preferred. In the case of layered compounds, the layered structure (laminated state) of the clay mineral may be collapsed in the non-halogen flame-retardant resin composition and its molded body, and the constituent layers may exist alone. Specific examples of clay minerals include kaolin minerals (kaolinite, nacrite, dickite, halloysite), mica clay minerals, smectites (montmorillonite, beidellite, saponite, hectorite, etc.), and mixed layer minerals. The silicate mineral preferably contains a cation, and preferably has a cation between the layers. The cation is usually Ca + , Na + , K + and the like metal cations. The clay mineral may be a natural product or a synthetic product obtained by hydrothermal synthesis, a melting method, a solid-phase method, or the like. The clay mineral may be a commercially available product (e.g., a complex) in which a part of the cations of the silicate contained therein is replaced by a quaternary ammonium cation derived from a quaternary ammonium salt described later. The clay mineral may be in a form contained in the clay. Examples of the clay include acid clay containing a large amount of montmorillonite, bentonite, and kaolin containing a large amount of kaolin minerals, with bentonite being preferred. The halogen-free flame-retardant resin composition of the present invention may contain one or more types of clay minerals. The content of the clay mineral in the halogen-free flame-retardant resin composition is appropriately determined taking into consideration the above total content, and may be, for example, 1 to 20 parts by mass per 100 parts by mass of the base rubber.

[0041] (Quaternary ammonium salt) The quaternary ammonium salt acts to enhance the dispersibility of the clay mineral in the base resin. From the viewpoint of further enhancing the dispersibility of the clay mineral, it is preferable that the clay mineral and the quaternary ammonium salt are used as a mixture or a complex in which they are mixed in advance. The quaternary ammonium salt is not particularly limited, and examples thereof include NR4 + X - In the formula, each R is independently a hydrogen atom, an alkyl group, a hydroxyalkyl group (-R 1 O.H., R. 1 represents an alkylene group. 2 O) n H(R 2 represents an alkylene group, and n is an integer of 1 to 20.) or an aryl group, provided that at least one of the four R's is an alkyl group, a hydroxyalkyl group, -(R 2 O) n H or an aryl group, and an alkyl group is preferable. The alkyl group that can be taken as R is not particularly limited, but an alkyl group having 1 to 20 carbon atoms is preferable. R 1 or R 2 The alkylene group that can be used as is not particularly limited, but an ethylene group is preferred. Multiple R in a single molecule may be the same or different. n is preferably an integer of 1 to 20, more preferably an integer of 1 to 10, further preferably an integer of 1 to 5, and particularly preferably 1. X - X indicates a counter ion. - is not particularly limited and various anions may be appropriately selected, but a halogen ion is preferred, for example, Cl - , Br - etc. The halogen-free flame-retardant resin composition of the present invention may contain one or more types of quaternary ammonium salt. The content of the quaternary ammonium salt in the halogen-free flame-retardant resin composition is appropriately determined in consideration of the above total content, and may be, for example, 0.2 to 12 parts by mass per 100 parts by mass of the base rubber.

[0042] <Other polymers> The halogen-free flame-retardant resin composition of the present invention may contain a polymer (regardless of resin, elastomer, or rubber) other than the polymer constituting the base resin. Examples include styrene-based elastomers, acrylic rubber, and ethylene propylene rubber. The content of the other polymer is appropriately determined within a range that does not impair the effects of the present invention, and can be, for example, 30% by mass or less relative to 100% by mass of the base resin.

[0043] <Other additives> The halogen-free flame-retardant resin composition of the present invention may contain various additives that are generally used in resin compositions, within the scope of the present invention. Examples of additives include flame retardant assistants, antioxidants (antioxidants), lubricants, crosslinking agents, crosslinking assistants, etc. The halogen-free flame-retardant resin composition may contain one or more types of each additive.

[0044] (Flame retardant assistant) The flame retardant aid is not particularly limited as long as it is one that is normally used in resin compositions, and known aids can be used. Examples of the flame retardant aid include melamine cyanurate, melamine isocyanurate, zinc sulfide, and zinc borate. Other examples include calcium oxide, magnesium oxide, aluminum oxide, aluminum nitride, aluminum borate whisker, basic magnesium carbonate, talc, and further boron nitride, silica (crystalline silica, amorphous silica, etc.), carbon, zinc oxide, tin oxide, titanium oxide, molybdenum oxide, antimony trioxide, quartz, white carbon, zinc hydroxystannate, and zinc stannate. Among these, it is preferable to use melamine cyanurate and zinc sulfide in combination. The (total) content of the flame retardant auxiliary in the halogen-free flame-retardant resin composition is set within a range that does not impair the effects of the present invention, and can be, for example, 5 to 100 parts by mass relative to 100 parts by mass of the base resin. In particular, the content of melamine cyanurate and melamine isocyanurate can be 5 to 50 parts by mass relative to 100 parts by mass of the base resin, and the content of zinc sulfide can be 1 to 10 parts by mass relative to 100 parts by mass of the base resin.

[0045] (Anti-aging agent) The antioxidant is not particularly limited, but examples thereof include amine antioxidants, phenol antioxidants, and sulfur antioxidants, with phenol antioxidants being preferred. The content of the antioxidant in the halogen-free flame-retardant resin composition is set within a range that does not impair the effects of the present invention, and can be, for example, 0.2 to 10 parts by mass per 100 parts by mass of the base resin.

[0046] (lubricant) The lubricant is not particularly limited, but examples thereof include silicone compounds, fatty acids, fatty acid metal salts, fatty acid amides, etc., with silicone compounds being preferred. The content of the lubricant in the halogen-free flame-retardant resin composition is set within a range that does not impair the effects of the present invention, and can be, for example, 0.5 to 10 parts by mass per 100 parts by mass of the base resin.

[0047] <Crosslinking agents and crosslinking assistants> When the non-halogen flame-retardant resin composition of the present invention is a crosslinkable composition, it may contain an appropriate crosslinking agent and further a crosslinking assistant depending on the crosslinking method. The crosslinking method applicable to the non-halogen flame-retardant resin composition of the present invention is not particularly limited, but is preferably an electron beam crosslinking method or a chemical crosslinking method. Examples of the chemical crosslinking method include phenol crosslinking, amine crosslinking, silane crosslinking, or peroxide crosslinking. The crosslinking agent and crosslinking assistant used in each crosslinking method can be any known one without any particular limitation.

[0048] <Physical properties or characteristics> The halogen-free flame-retardant resin composition of the present invention may be a crosslinked resin composition or a non-crosslinked resin composition, and is appropriately selected depending on the application and required properties. When used as a wiring material, particularly as a coating material for optical cables, it is preferable to use a non-crosslinked resin composition. (Moldability) The non-halogenous flame-retardant resin composition of the present invention having the above composition exhibits a MFR of 0.3 g / 10 min or more (measurement temperature 190° C., load 10 kg) and exhibits high moldability. Therefore, when molding is performed using the non-halogenous flame-retardant resin composition of the present invention, smooth molding is possible with a load within the allowable range of the molding machine without placing an excessive load on the molding machine. In addition, by utilizing the high moldability, a molded body (coating layer) can be formed, and preferably a molded body of a predetermined shape and size can be formed.

[0049] (Flame retardant) The non-halogen-based flame-retardant resin composition of the present invention and its molded article have a high level of flame retardancy, with no dripping and a flame-extinguishing time of 90 seconds or less, in a flame retardancy test in the Examples described below.

[0050] (Mechanical properties) The tensile strength achieved by the halogen-free flame-retardant resin composition of the present invention and its molded article varies depending on the application and required characteristics, and is not definite, but is preferably 5 MPa or more, more preferably 7 to 20 MPa. The breaking elongation varies depending on the application and required characteristics, and is not definite, but is preferably 100% or more, more preferably 150% or more, and the upper limit is not particularly limited, but about 200% is practical. In addition, the 100% modulus (sometimes written as 100% M) varies depending on the application and required characteristics, and is not definite, but is preferably 4 MPa or more, more preferably 5 to 10 MPa. The above tensile strength, breaking elongation and 100% modulus are values ​​measured by the measurement method described in the examples below.

[0051] <Applications of halogen-free flame-retardant resin compositions> The halogen-free flame-retardant resin composition of the present invention exhibits the above-mentioned excellent properties, and therefore can be suitably used as a material for forming wiring materials, particularly a coating layer for wiring materials. It can also be applied to general molded products (sealing materials, packing, etc.). The molding method at this time can be any of various known molding methods without particular limitations, but extrusion molding and injection molding are preferred, taking advantage of the excellent moldability (MFR).

[0052] <Method for preparing the halogen-free flame-retardant resin composition of the present invention> The halogen-free flame-retardant resin composition of the present invention can be prepared by melt-kneading a base resin, a metal hydrate, a clay mineral, a quaternary ammonium salt, and optionally other additives. The kneading method is not particularly limited as long as it is a method that is usually adopted for preparing a rubber or resin composition. For example, various mixing devices such as a single-screw kneader, a twin-screw kneader, a roll, a Banbury mixer, and various kneaders can be used for mixing. Kneading conditions such as kneading temperature and kneading time are not particularly limited and can be appropriately set within a temperature range equal to or higher than the melting temperature of the base resin. The kneading temperature is preferably, for example, 120 to 220°C. By melt kneading, an uncrosslinked or non-crosslinked resin composition in which each component is uniformly dispersed (mixed) can be obtained.

[0053] In mixing the components, the components can be melt-kneaded at once, or can be mixed in a suitable order. In the present invention, it is preferable to mix the clay mineral and the quaternary ammonium salt in advance to form a mixture or complex, and then knead the mixture or complex with the components. Commercially available mixtures or complexes of quaternary ammonium salts and clay minerals can also be used. It is believed that when such mixtures or complexes are kneaded with a base resin, the clay mineral aggregates are broken down by the shear force during kneading, and a resin composition in which the clay mineral is more highly dispersed can be obtained. According to a preferred preparation method, the non-halogen-based flame-retardant resin composition of the present invention is prepared by mixing a clay mineral which is previously mixed with a quaternary ammonium salt (treated (mixed) with a quaternary ammonium salt), a base resin, and a metal hydrate in the above-mentioned specific ratio.

[0054] [Wiring material] A wiring material using a tubular molding formed from the halogen-free flame-retardant resin composition of the present invention as a covering layer will be described below. The wiring material of the present invention has a coating layer (including an insulating layer, a sheath, etc.) formed of the halogen-free flame-retardant resin composition of the present invention on the outer peripheral surface of the conductor. This wiring material has excellent flame retardancy, mechanical properties, and wiring properties. The wiring material of the present invention may have at least one coating layer made of the non-halogen flame-retardant resin composition of the present invention on the outer circumferential surface of a conductor (including an optical fiber core, an optical fiber core bundle, etc.), and the other configurations may be the same as those of a normal wiring material. For example, an insulated electric wire having at least one coating layer on the outer circumferential surface of a conductor, a cable in which a sheath is formed as a coating layer on the outer circumferential surface of such an insulated electric wire or a bundle of electric wires in which a plurality of such insulated electric wires are bundled, etc. may be mentioned. In addition, the coating layer made of the non-halogen flame-retardant resin composition of the present invention may be provided directly on the outer circumferential surface of the conductor, or may be provided indirectly via another layer such as an adhesive layer. The coating layer may be a single layer or multiple layers, and in the case of multiple layers, at least one layer may be formed of the non-halogen flame-retardant resin composition of the present invention. In addition, the sheath of the cable may be formed of the non-halogen flame-retardant resin composition of the present invention.

[0055] As the conductor, a suitable conductor according to the wiring material can be used. For example, a solid wire conductor or a stranded wire conductor (including a stranded wire in which tensile strength fibers are vertically attached or twisted together) can be used as appropriate. For example, a bare wire or a tin-plated or enamel-coated conductor can be used as a conductor for an insulated electric wire or the like. Metal materials forming the conductor include soft copper, copper alloy, aluminum, etc. The outer diameter of the conductor is determined as appropriate according to the application, etc., and can be set to the same as that of a normal wiring material used for each application. For example, it can be 0.5 to 4.0 mm. In addition to the above conductors, examples of the conductor in the optical cable include an optical fiber core, an optical fiber core bundle in which a plurality of optical fiber cores are bundled, and further, an electric wire bundle in which a plurality of the above insulated electric wires are bundled. The thickness (wall thickness) of the coating layer is determined appropriately depending on the application, etc., but can be set to a thickness similar to that of ordinary wiring materials used for each application. For example, for insulated wires, etc., it is usually set to about 0.15 to 10 mm.

[0056] Examples of wiring materials include insulated electric wires or cables, (electric) cords, optical fiber cords, optical cables, etc. These include wiring materials used for internal wiring or external wiring of electric / electronic devices, wiring materials arranged indoors, and wiring materials arranged outdoors. The wiring material of the present invention can be preferably used as an insulated electric wire or cable for vehicles (automobiles, railway cars, etc.), electric wires or cables for communication, optical cables for communication, or electric wires or cables for power. In particular, optical cables and the like used for transmitting large amounts of information arranged in data centers, etc. are preferred. Examples of the wiring material of the present invention include an electric wire shown in Figure 1 of Patent Document 1 in which the insulation layer 3 is formed from the non-halogenous flame-retardant resin composition of the present invention, and a cable shown in Figure 2 of Patent Document 2 in which the insulation 23 and / or sheath 24 are formed from the non-halogenous flame-retardant resin composition of the present invention. Further examples include an optical cable shown in Figure 1 of Patent Document 2 in which the covering layer 20 is formed from the non-halogenous flame-retardant resin composition of the present invention, and an optical cable shown in Figure 2 of Patent Document 2 in which the covering layer 21 is formed from the non-halogenous flame-retardant resin composition of the present invention.

[0057] An embodiment in which the wiring material is an optical cable will be described with reference to FIG. FIG. 1 shows a cross section perpendicular to the longitudinal direction of an optical cable. The optical cable 1 shown in FIG. 1 has an optical fiber 10 as a conductor, and a coating layer (sheath) 20 formed around (on the outer surface of) the optical fiber 10 from the halogen-free flame-retardant resin composition of the present invention. As long as the optical cable 1 has the above-mentioned configuration, other configurations are not particularly limited, and the number of coating layers 20, the number of optical fiber cores 10, the arrangement of the optical fiber cores 10, etc. can be appropriately set according to the application. When the coating layer has a multi-layer structure, it is sufficient that at least one coating layer is formed from the halogen-free flame-retardant resin composition of the present invention. In this case, other layers, such as an intermediate layer, can be formed from a resin or a composition thereof that is usually used in optical cables. The optical cable 1 has a single-core optical fiber core 10, and this optical fiber core 10 can be a normal one without any particular restrictions, and can be an optical fiber itself, or an optical fiber core having an insulating tape wound or a coating layer on the outer surface thereof. When the optical fiber core has a coating layer or the like, this corresponds to the case in the configuration shown in FIG. 1 above where the coating layer has a multi-layer structure. A normal optical fiber core can be used. The optical fiber core is preferably a quartz fiber core. The outer diameter of the optical cable 1 and the optical fiber core 10 is appropriately set depending on the application, etc. The thickness of the coating layer, particularly the coating layer 20 formed from the non-halogenous flame-retardant resin composition of the present invention, is appropriately set depending on the application, etc., but is preferably 0.2 to 5 mm in order to exhibit the excellent properties of the non-halogenous flame-retardant resin composition of the present invention.

[0058] The optical cable 1 may have a tension member (not shown in FIG. 1). The tension member may be any tension member that is normally applied to optical cables, without any particular limitation. The number and positions of the tension members are also not particularly limited and may be set appropriately. For example, the tension members may be arranged so as to cover the outer periphery of the optical fiber core, or may be arranged at a distance from the optical fiber core.

[0059] FIG. 2 is a diagram showing a cross section perpendicular to the longitudinal direction of another embodiment of the wiring material (optical cable) of the present invention. As shown in FIG. 1, this optical cable 2 has an optical fiber core bundle 11 as a conductor, a nonwoven fabric tape 12 wound around (on the outer surface) of the optical fiber core bundle 11, a sheath 21 formed around (on the outer surface) of the nonwoven fabric tape 12 from the halogen-free flame-retardant resin composition of the present invention, and two tension members 13 embedded in the sheath 21 along the optical fiber core bundle 11. As long as the optical cable 2 has the above-mentioned configuration, other configurations are not particularly limited, and the number of optical fiber cores constituting the optical fiber core bundle 11, the presence or absence of the nonwoven fabric tape 12, the number and arrangement of the tension members 13, the number of layers of the sheath 21, etc. can be appropriately set according to the application. When the sheath 21 has a multi-layer structure, it is sufficient that at least one layer of the sheath 21 is formed from the non-halogenous flame-retardant resin composition of the present invention. In this case, other layers, for example, an intermediate layer, can be formed from a resin or a composition thereof that is usually used in optical cables. The optical cable 2 has an optical fiber core bundle 11, and this optical fiber core bundle 11 can be a normal one without any particular limitation. The number of optical fiber cores constituting the optical fiber core bundle 11 is usually two or more, but is appropriately set according to the performance and application, and for high performance applications, it can be, for example, 288, 864, or even 1728. The optical fiber core bundle 11 may be a bundle of multiple optical fiber cores, and may be a twisted wire or a drawn wire, and is appropriately set. On the other hand, the optical fiber core bundle 11 can also be a single-core optical fiber core. Each optical fiber core may be an optical fiber bare wire itself, or may have an insulating tape wound body or a coating layer on the outer surface of the optical fiber bare wire. A normal optical fiber bare wire can be used, and for example, a quartz fiber bare wire is preferable. A nonwoven fabric tape 12 is wound around the optical fiber core bundle 11 to collectively cover the optical fiber core bundle 11. Instead of the nonwoven fabric tape 12, a commonly used material such as an insulating tape may be used as appropriate. A single-layer sheath 21 is provided around the nonwoven fabric tape 12, and two tension members 13 are embedded inside it so that the central angle is about 180° (facing each other with the optical fiber core bundle 11 in between). The tension members 13 can be ones that are normally used in optical cables, such as filaments made of metal, resin, etc., without any particular restrictions. The outer diameters of the optical cable 2, the optical fiber core bundle 11, and the tension member 13 are set appropriately depending on the application, etc. The thickness of the sheath 21, particularly the sheath 21 formed from the non-halogenous flame-retardant resin composition of the present invention, is set appropriately depending on the application, etc., but is preferably 0.2 to 5 mm in order to exhibit the excellent properties of the non-halogenous flame-retardant resin composition of the present invention.

[0060] <Manufacturing method of wiring material> The wiring material of the present invention can be produced by any suitable method, but is preferably produced by disposing the halogen-free flame-retardant resin composition of the present invention on the outer peripheral surface of a conductor and appropriately carrying out a crosslinking reaction treatment.

[0061] The method of disposing the non-halogenous flame-retardant resin composition of the present invention on the outer peripheral surface of the conductor may be any method capable of covering the conductor with the non-halogenous flame-retardant resin composition, and any suitable molding method may be applied. For example, the molding method may be extrusion molding using an extruder, injection molding using an injection molding machine, or molding using other molding machines. In the present invention, extrusion molding or injection molding is preferred, taking advantage of the high moldability, and extrusion molding in which the conductor and the non-halogenous flame-retardant resin composition are co-extruded is preferred. The extrusion molding can be carried out using a general-purpose extruder. The extrusion molding temperature is appropriately set according to various conditions such as the melting point and extrusion speed (take-off speed) of the non-halogen flame-retardant resin composition. When the non-halogen flame-retardant resin composition of the present invention is a crosslinkable resin composition, the temperature is set to a temperature lower than the temperature at which the crosslinking reaction occurs (for example, the decomposition temperature of the organic peroxide) in order to suppress the occurrence of the crosslinking reaction. For example, it is preferable that such an extrusion molding temperature is set to the same temperature as the kneading temperature in the preparation method of the non-halogen flame-retardant resin composition of the present invention. Other extrusion molding conditions are appropriately set. The method of disposing the non-halogen-based flame-retardant resin composition of the present invention on the outer peripheral surface of a conductor (disposing the non-halogen-based flame-retardant resin composition) can also be carried out as a series of steps (all at once) using an extruder, consecutively to the method of preparing the non-halogen-based flame-retardant resin composition of the present invention (preparation of the non-halogen-based flame-retardant resin composition in an extruder).

[0062] When the non-halogenous flame-retardant resin composition of the present invention is a crosslinkable resin composition, the non-halogenous flame-retardant resin composition arranged on the outer peripheral surface of the conductor is then subjected to a crosslinking reaction treatment. This crosslinking reaction treatment can be applied without any particular restrictions to the method and conditions usually applied to each crosslinking method applied to the crosslinkable composition. For example, in the case of peroxide crosslinking, a method can be mentioned in which a heating device such as a heating furnace or a heating tube is used to heat a conductor having the non-halogenous flame-retardant resin composition of the present invention arranged on the outer peripheral surface (extrusion molding, extrusion coating) to a temperature equal to or higher than the temperature at which the peroxide decomposes. In the case of electron beam crosslinking, a method can be mentioned in which an electron beam is irradiated at a dose of, for example, 1 to 30 Mrad. In the case of silane crosslinking, the conductor is brought into contact with water.

[0063] In this manner, using the halogen-free flame-retardant resin composition of the present invention, wiring materials having a coating layer with excellent flame retardancy and mechanical properties can be produced with high productivity without placing excessive load on the molding machine. EXAMPLES

[0064] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these. In the following Tables 1-1 and 1-2 (collectively referred to as Table 1), the numerical values ​​relating to the blending amount of each example are based on mass unless otherwise specified. Note that blank spaces indicate that the blending amount of the corresponding component is 0 mass% or 0 mass parts.

[0065] Working Example , reference example And Comparative Example (Hereinafter referred to as "Examples and Comparative Examples.") Details of each compound used are shown below. <Ethylene vinyl acetate copolymer> EV180: Product name, manufactured by Mitsui Dow Polychemicals, MFR 0.2, VA amount 33 V421: Trade name, manufactured by Mitsui Dow Polychemicals, MFR4, VA content 28 EV260: Product name, Mitsui Dow Polychemicals, MFR6, VA content 28 EV450: Product name, manufactured by Mitsui Dow Polychemicals, MFR15, VA content 25 V406: Product name, Mitsui Dow Polychemicals, MFR20, VA content 20 EV150: Product name, manufactured by Mitsui Dow Polychemicals, MFR30, VA content 33 The MFR is a value measured at a temperature of 190° C. and a load of 2.16 kg, and is expressed in units of g / 10 min. The VA amount is the vinyl acetate content in the ethylene-vinyl acetate copolymer, and is expressed in units of mass %.

[0066] <Acid-modified polyolefin polymer> L6100M: Product name, maleic acid modified polyethylene, manufactured by Japan Polyethylene Corporation <α-olefin polymer> LLDPE: Evolu 0540 (product name), manufactured by Prime Polymer, MFR 3.8 Random PP: PM921V (product name), manufactured by SunAllomer, MFR25 EEA: Rexpearl A1150 (product name), manufactured by Japan Polyethylene Co., Ltd., polyolefin copolymer (ethylene-ethyl metharylate copolymer) having an acid copolymerization component, MFR (190°C, load 2.16 kg) 0.8, ethyl metharylate (EA) content 15% <Metal hydrate> Aluminum hydroxide: BF013S (product name), manufactured by Nippon Light Metals Co., Ltd., average particle size 1 μm, surface treatment agent: fatty acid <Clay minerals and quaternary ammonium salts> BYK-MAX CT 4260 (trade name), manufactured by BYK, aluminum silicate treated with ammonium salt (used as a mixture or complex of the clay mineral and quaternary ammonium salt described above). Kunipia F (product name), manufactured by Kunimine Kogyo Co., Ltd. <Other additives> Lubricant: Ginioplast Gum (product name), manufactured by Asahi Kasei Wacker Silicone Co., Ltd., silicone gum Anti-aging agent: Irganox 1010 (product name), manufactured by BASF Japan, pentaerythritol tetrakis-(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate) Melamine cyanurate: MC6000 (trade name), manufactured by Nissan Chemical Industries, Ltd., flame retardant aid Zinc sulfide: Sahatori's HD-S (trade name), manufactured by Sactkeben, flame retardant aid Zinc borate: SZB-2335 (trade name), manufactured by Sakai Chemical Industry Co., Ltd., flame retardant aid

[0067] [Examples 1 to 14 (however, Examples 5 and 11 、13 are missing numbers, the same applies hereinafter), Reference Example 1 ~3 and Comparative Examples 1 to 10] (Preparation and Molding of Non-Halogen Flame Retardant Resin Composition) Each component shown in Table 1 was put into a 2L intensive mixer (manufactured by Nippon Roll Co., Ltd.), kneading was started at 140 to 150 °C, and kneaded for 7 minutes at a rotor rotation speed of 40 to 45 rpm. Subsequently, kneading was carried out at 170 to 180 °C for 3 minutes, and discharged at an internal temperature of 170 to 180 °C to prepare a non-halogen flame retardant resin composition. Next, this non-halogen flame retardant resin composition was press-molded into a sheet with a thickness of 3 mm using a roll processing machine (manufactured by Yamakoshi Co., Ltd.) to obtain a sheet-like test piece. Also, the above non-halogen flame retardant resin composition was pelletized.

[0068] Regarding the MFR of the prepared non-halogen flame retardant resin composition, each sheet-like test piece manufactured, or the test piece prepared from the pellets, the following tests were conducted, and the results are shown in Table 1.

[0069] <Measurement of MFR> Regarding the prepared non-halogen flame retardant resin composition, based on the method specified in JIS K 7210-1, the MFR was measured under the conditions of a measurement temperature of 190 °C and a load of 10 kg.

[0070] <Labo Plastomill Test> Into a kneading and extrusion molding evaluation test apparatus: Labo Plastomill 10C100 (product name, manufactured by Toyo Seiki Co., Ltd.), 250 cc (filling amount 80%) of the prepared non-halogen flame retardant resin composition was charged, and within 30 seconds after charging and 40 seconds after the start of preheating, the test was started under the conditions of a temperature of 170 °C and a rotation speed of 40 rpm. During the test, the maximum torque and the steady torque after 4 to 6 minutes were compared with a standard material with a proven track record of processing to evaluate the kneading load. The evaluation was performed according to the following evaluation criteria, with "◎" and "◯" indicating the passing level of the test. - Evaluation Criteria - ◎: Steady torque 80N m or less (sufficiently low, melt viscosity is also sufficiently low) Good: Steady-state torque of over 80 N m and up to 120 N m (the steady-state torque is equivalent to that of proven materials and there are no problems with workability) ×: Steady-state torque exceeds 120 N m (high steady-state torque makes extrusion difficult)

[0071] <Mechanical property testing> (Preparation of test specimens) Using an extruder (cylinder diameter 25 mm, L / D=22) with a die temperature set at 170° C., pellets of the halogen-free flame-retardant resin composition prepared in each Example and Comparative Example were extruded into a tape-shaped sample having a thickness of 1 mm and a width of 25 mm. Note that Comparative Examples 1, 6, 8, and 10 could not be extruded. From this tape sample, a "No. 3 dumbbell test piece" was made according to JIS K 6251 (2010), with a thickness of 1 mm. (Mechanical property measurements) Using the prepared test pieces, a tensile test was carried out under the following conditions in accordance with the method specified in JIS K 6251, and the tensile strength, 100% modulus, and breaking elongation were measured. The passing level for this test is a tensile strength of 5 MPa or more. The 100% modulus must be 4 MPa or more to pass this test. The passing level for this test is a breaking elongation of 100% or more. - Test conditions - Distance between gauge lines: 20mm Tensile speed: 200mm / min Other conditions are in accordance with those specified in JIS K 6251.

[0072] <Flame retardancy test> (Preparation of test specimens) A rectangular test piece having a width of 6 mm, a thickness of 3 mm, and a length of 170 mm was prepared as follows. That is, pellets of the halogen-free flame-retardant resin composition prepared in each of the Examples and Comparative Examples were molded into a sheet having a thickness of 3 mm using a heat press molding machine, and the sheet was cut out to obtain a predetermined test piece. (Flame Retardancy Test) The prepared test specimen was placed vertically, and the flame from a burner with an outer flame length adjusted to 20 mm was applied to the lowest end of the test specimen for 30 seconds (based on the UL94 combustion test). Propane gas was used as the combustion gas. The test piece was then burned, and the time from the start of flame contact to the end of flame (extinction time) was measured, while the burning state was observed to confirm the presence or absence and the extent of dripping of the coating layer from the test piece. The results were used to evaluate the flame retardancy according to the following evaluation criteria. In addition, in Comparative Examples 2 and 3, dripping was so severe that it was impossible to continue the test, and therefore "-" was entered in the "flame-extinguishing time" column. - Evaluation Criteria - (1) Flame-extinguishing time The test was deemed to pass if the flame-extinguishing time was within 90 seconds. (2) Presence or absence of dripping and its extent 〇: No dripping (extinguishes flames. Prevents fire from spreading without dripping) ×: Dripping occurred (flame extinguished or spread after dripping)

[0073] [Table 1-1]

[0074] [Table 1-2]

[0075] As is clear from the results shown in Table 1, the halogen-free flame-retardant resin compositions of Comparative Examples 1 to 10, which do not contain 100 to 250 parts by mass of metal hydrate and 2 to 30 parts by mass of clay mineral and quaternary ammonium salt relative to a base resin having a specific composition, have low MFR and poor moldability, or are unable to achieve both excellent flame retardancy and mechanical properties. In contrast, the non-halogenous flame-retardant resin compositions of Examples 1 to 14, which contain a base resin containing 60% by mass or more of ethylene vinyl acetate exhibiting a specific MFR, 100 to 250 parts by mass of a metal hydrate, and 2 to 30 parts by mass of a clay mineral and a quaternary ammonium salt, all have an MFR of 0.3 g / 10 min or more, excellent moldability, and excellent flame retardancy and mechanical properties. These test results show that wiring materials having a coating layer formed from the non-halogenous flame-retardant resin compositions of Examples 1 to 14 can be produced with high productivity and exhibit excellent flame retardancy and mechanical properties. [Explanation of symbols]

[0076] 1, 2 Optical cable 10 Optical fiber core 11 Optical fiber core bundle 12 Non-woven tape 13 Tension member 20 Covering layer 21 Sheath

Claims

1. For 100 parts by mass of a base resin containing 60 to 95% by mass of an ethylene-vinyl acetate copolymer having a melt flow rate (measurement temperature: 190° C., load: 2.16 kg) of 2 to 15 g / 10 min, 5 to 20% by mass of an acid-modified polyolefin polymer, and 20% by mass or less of an α-olefin polymer, The metal hydrate contains 100 to 250 parts by mass, a clay mineral and a quaternary ammonium salt in a total amount of 8 to 30 parts by mass, 5 to 50 parts by mass of melamine cyanurate, and 1 to 10 parts by mass of zinc sulfide, the metal hydrate containing aluminum hydroxide, and A halogen-free flame-retardant resin composition having a melt flow rate (measurement temperature: 190° C., load: 10 kg) of 0.3 g / 10 min or more.

2. The halogen-free flame-retardant resin composition according to claim 1, wherein the content of the ethylene-vinyl acetate copolymer is 60 to 90% by mass, and the content of the α-olefin polymer is 5 to 20% by mass.

3. The halogen-free flame-retardant resin composition according to claim 1 or 2, wherein the α-olefin polymer comprises at least one of polyethylene and polypropylene.

4. The non-halogen-based flame-retardant resin composition according to any one of claims 1 to 3, wherein the acid-modified polyolefin polymer comprises at least one of maleic anhydride-modified polyethylene, acrylic acid-modified polyethylene, maleic anhydride-modified polypropylene, and acrylic acid-modified polypropylene.

5. A wiring material having a coating layer on an outer peripheral surface of a conductor, A wiring material, wherein the coating layer is formed from the halogen-free flame-retardant resin composition according to any one of claims 1 to 4.

6. The wiring material according to claim 5 , which is an insulated wire or a power cable.

7. The wiring material according to claim 5 or 6, which is an optical cable.

Citation Information

Patent Citations

  • flame retardant composition

    JP2006519895A

  • Flame-retardant composition

    JP2007505990A

  • Flame-retardant filler for plastics

    JP2007532461A

  • Halogen-free flame-retardant resin composition and electric wire / cable using the same

    JP2009084524A

  • Fiber-reinforced resin material, resin molding and method of producing fiber-reinforced resin material

    JP2015224313A